#### Answer

$x^{40}$

#### Work Step by Step

Use the rule $(a^m)^n=a^{mn}$ to obtain:
$(x^{-4})^{-10}=x^{-4(-10)}=x^{40}$

Published by
Pearson

ISBN 10:
0-32184-874-8

ISBN 13:
978-0-32184-874-1

$x^{40}$

Use the rule $(a^m)^n=a^{mn}$ to obtain:
$(x^{-4})^{-10}=x^{-4(-10)}=x^{40}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.